2014
DOI: 10.1177/1420326x14525062
|View full text |Cite
|
Sign up to set email alerts
|

Power performance of photovoltaic-integrated lightshelf systems

Abstract: The lightshelf system, a sort of daylighting device, has been applied to improve the visual environment by optimal light distributions and intense illumination levels of an interior. Also, the photovoltaic is one of the most important sustainable technologies applicable to architectures. The purpose of this study was to evaluate basic data to develop the photovoltaic (PV)-integrated lightshelf systems for office buildings. The performance of PV lightshelves was evaluated by using 1/5 scaled model. The scaled o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…Because of the high efficiency offered by the daylighting systems, various studies have focused on performance improvement of these systems. [2][3][4] A light-shelf is a daylighting system that is an appropriate means of reducing indoor lighting energy use as it introduces external natural light deep into the interior of a building through a reflector. However, in most ongoing studies of light-shelves, the reflector of the light-shelf has a flat or a simple curved shape, [3][4][5][6][7][8][9][10] and thus its performance decreases depending on external environmental conditions such as the azimuth and altitude of the Sun.…”
Section: Research Background and Purposementioning
confidence: 99%
“…Because of the high efficiency offered by the daylighting systems, various studies have focused on performance improvement of these systems. [2][3][4] A light-shelf is a daylighting system that is an appropriate means of reducing indoor lighting energy use as it introduces external natural light deep into the interior of a building through a reflector. However, in most ongoing studies of light-shelves, the reflector of the light-shelf has a flat or a simple curved shape, [3][4][5][6][7][8][9][10] and thus its performance decreases depending on external environmental conditions such as the azimuth and altitude of the Sun.…”
Section: Research Background and Purposementioning
confidence: 99%
“…However, in previous light-shelf systems, the direction of incoming light was determined by the solar altitude and azimuth, thereby limiting the lighting performance efficiency of these light-shelf systems. Furthermore, studies on previous light-shelf systems focused mainly on simple variables such as the width, angle, installation position, and height of the lightshelf [2][3][4][5][6][7][8][9][10][11][12][13] without considering information on the location of the occupant. In particular, the window design guideline for building energy saving 14 has shown that a window-to-wall ratio of less than 40% is efficient in energy saving; therefore, in the case of light-shelf systems using natural light, this will act as an efficiencylimiting factor.…”
Section: Research Background and Purposementioning
confidence: 99%
“…As shown in Table 1 , previous studies related to light shelves [ 5 , 6 , 7 , 8 , 12 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 ] controlled the variables associated with light shelves or changed their shape to improve daylighting performance. Recent studies integrated various moving or operational technologies, including IT, and applied other elements to light shelves, such as awnings and PV modules.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies integrated various moving or operational technologies, including IT, and applied other elements to light shelves, such as awnings and PV modules. A study that combined dual PV modules with a light shelf [ 17 ] indicated improved building energy reduction efficiency by attaching the module on part of, or in front of, the light shelf reflector. They found that installing PV modules on part of the light shelf, instead of installing the modules in front of the light shelf, was more advantageous in terms of saving building energy [ 12 ].…”
Section: Introductionmentioning
confidence: 99%